Treatment Planning of Intensity Modulated Radiation Therapy (IMRT/VMAT) study aid - Sukhikh specialist in the field of nuclear energy Associate Professor of Tomsk Polytechnic University, Candidate of Physical and Mathematical Sciences; Sutygina specialist in the field of nuclear technologies engineer of Tomsk Polytechnic University; Stakhova specialist in the field of nuclear technologies engineer of Tomsk Polytechnic University; Sagov nuclear technology specialist engineer of Tomsk Polytechnic University (TPU Publishing House, 2024)
The manual provides an overview of the fundamentals of treatment planning of Intensity Modulated Radiation Therapy (IMRT/VMAT), which is based on international recommendations used by cancer care clinics around the world. It includes a concise theoretical foundation, a systematic explanation of practical aspects, and procedures for the preparation and dosimetric planning of intensity modulated radiation therapy. Additionally, it offers methodological recommendations on treatment planning in various tumor locations using computer systems such as PlanUNC, Monaco, Eclipse, and matRad, which are essential for laboratory work in the courses "Radiation Treatment Planning". The book is intended for students pursuing studies in 14.04.02 "Nuclear physics and technologies" programs and medical physicists.